PENGARUH MODEL COURSE REVIEW HORAY BERBANTUAN MEDIA PAPINKA TERHADAP HASIL BELAJAR SISWA KELAS V DI SD NEGERI PATI WETAN 03 - Zulva Aziza, Denise; Kamdun; Kironoratri, Lintang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
This article aims to determine the differences in the average student learning outcomes between before and after using the Course Review Horay model assisted by PAPINKA and to determine the increase in student learning outcomes after using the Course Review Horay model assisted by PAPINKA media. This research is a quantitative study with a Pre-Experimental Design in the form of One Group Pretest-Posttest Design. Data analysis techniques were analyzed using paired sample t-test and N-gain test. The results of testing the hypothesis from the paired sample t-test mean value of the pretest is 63.92 while the average value of the posttest is 84.64. It can be seen that the posttest average from the results of the learning outcomes test scores is greater than the pretest average. Shows the Sig.(2-tailed) value, namely 0.000 <0.05, then Ho is rejected and Ha is accepted. And the N-gain value is 0.61 which means the criteria are moderate. Meanwhile, the percentage of the N-gain value is 61% which shows that the interpretation can be categorized as quite effective. Thus there is a difference in the average student learning outcomes between before and after using the Course Review Horay model assisted by PAPINKA media and there is an increase in student learning outcomes after using the Course Review Horay model assisted by PAPINKA media Keyword : Learning Outcomes, Course Review Horay, PAPINKA (Heat Transfer Board)